Peningkatan Efikasi Cendawan Lecanicillium lecanii untuk Mengendalikan Telur Hama Kepik Coklat pada Kedelai - Prayogo, Yusmani; Santoso, Teguh; Kartosuwondo, Utomo; Sudirman, Lisdar I. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Lecanicillium lecanii is considered as an effective entomopathogenic fungi to control eggs of brown stink bug on soybean. Its efficacy is indicated by reducing the level of hatching of brown stink bug eggs. One factor affecting the efficacy of the entomopathogen in the field is its intolerant to sunlight exposure. A research was conducted in the screen house of the Indonesian Legumes and Tuber Crops Research Institute (ILETRI), Malang, from March to August 2008. The study was aimed at determining the effect of addition of vegetable oils on the efficacy of lecanii to control stink bug eggs on soybean. The trial was arranged in a randomized complete design with two factors. The first factor consisted of three vegetable oils i.e, peanut oil, soybean oil, and coconut oil. The second factor consisted of four oil concentration i.e; 2 ml/l, 5 ml/l, 10 ml/l, and without oil (control). Result showed that addition of vegetable oils as adjuvant increased significantly the growth and development of the entomopathogen, as indicated by the increase of colony diameter and number of conidia of lecanii in vitro. The fungal conidia persisted on the soybean plants until seven days after the adjuvant application at the rate of 10 ml/l water, while the conidia persisted only for one day on plants which was not applied with the vegetable oils. Hatchability of the brown stink bug eggs was only 20% when peanut oil was used as an adjuvant. Not all hatched eggs of the brown stink bug developed into adult, hence, the number of adult bugs that cause damages on soybean pods were reduced. In general, the addition of vegetable oil increased efficacy of the entomopathogen up to 40%. Among the vegetable oils tested, peanut oil was the most effective to increase the efficacy of lecanii to control brown stink bug egg on soybean.